GREETING SYSTEM IN BANDA NAIRA SPEECH COMMUNITY (A SOCIOLINGUISTIC REVIEW) - Mujiati La Saadi; Ernawati Ernawati (Universitas Brawijaya, 2020)
Greeting activities in social interactions create the use of greetings words. Greeting word is a lingual unit in the form of a word or group of words used in social interactions to address the interlocutor. The greeting word, referring to the personal pronoun of the second person in a conversation, is generally influenced by the speaker, the interlocutor, and the relationship between the two. This study aimed to describe the forms of greeting in the Banda Naira speech community and the factors that influence the use of greetings. This research used a descriptive qualitative method. The data used are greeting words. This research used distribution technique to analyze the data. The Banda Naira community uses forms of greeting divided into kinship terms and non-kinship terms. The usage distribution of kinship terms, referring to a person with and without familial ties, is often followed by the name of the other person. The usage of kinship terms is influenced by the multicultural nature of the Banda Naira community.